Close-In Blasting at the Tri-Met Light Rail Tunnels in Portland, Oregon - Gordon F. Revey; Don Z. Painter (International Society of Explosives Engineers, 1995)
Frontier/Traylor Joint Venture is presently constructing a section of the Tri-County Metropolitan Transit District of Oregon's (TRI-MET) Westside Light Rail system. This new section will extend Portland's existing transit system to the western suburbs of Beaverton and Hillsboro. The drill-blast excavations at this project include 10,000 feet of 20 foot tunnel, 18 cross passages, three shafts, an underground railway station, and a U-wall open cut. From a blast designer's perspective, this job has been extremely challenging. Blast vibration is limited to 0.5 ips at 200 feet or at the nearest structure, and airblast is limited to 129 dB -- linear peak and 96 dB -- C scale. The tunnels pass under heavily built up areas and have top of tunnel to surface cover distances as low as 70 feet. Surface blasting in the 26,000 cubic yard U-wall excavation was limited to five short nighttime periods due to its proximity to the very busy highway 26.